De novo design of orthogonal far-red, orange, and green fluorophore-binding proteins for multiplexed imaging - Long Tran; Steffen Klein; David Juergens; Shajesh Sharma; Justin Decarreau; Gyu Rie Lee; Yujia Wang; Wei Chen; Asim K. Bera; Alex Kang; Jon Woods; Emily Joyce; et al. (Science, 2026)
Fluorescent proteins and small-molecule dyes offer complementary advantages for biological imaging: proteins are amenable to genetic tagging, whereas dyes provide superior brightness and photostability. To combine these strengths, we used de novo protein design to generate small, nanomolar-affinity, high-selectivity binders (NovoTags) for three cell-permeable dyes spanning the visible spectrum. We show that the NovoTag fluorescent lifetimes can be tuned and demonstrate their application in lifetime and wavelength-based multiplexed fluorescence imaging. We further design a two-chain NovoTag that functions as a chemically induced dimerization system with fluorescent readout in living cells, or as a minimally perturbing proximity probe in fixed cells. Our approach combines the advantages of fluorescent proteins and small-molecule dyes, expanding the toolkit for cellular imaging.